The Role of BDNF in the Neuroimmune Axis Regulation of Mood Disorders - Jin, Yang; Sun, Li Hua; Yang, Wei; Cui, Ran Ji; Xu, Song Bai (Frontiers in Neurology, 2019)
Neuroimmune system plays a crucial role in the regulation of mood disorders. Moreover, recent studies show that brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family, is a key regulator in the neuroimmune axis. However, the potential mechanism of BDNF action in the neuroimmune axis regulation of mood disorders remains unclear. Therefore, in this review we focus on the recent progress of BDNF in influencing mood disorders by participating in alterations of the neuroimmune axis. It may provide evidence for future studies in this field.